2021
DOI: 10.1055/s-0041-1728818
|View full text |Cite
|
Sign up to set email alerts
|

Midtrimester Cervical Length in Low-Risk Nulliparous Women for the Prediction of Spontaneous Preterm Birth: Should We Consider a New Definition of Short Cervix?

Abstract: Objective The study aimed to estimate the predictive value of midtrimester cervical length (CL) and the optimal cut-off of CL that should be applied with asymptomatic nulliparous women for the prediction of spontaneous preterm birth (sPTB). Study Design This is a prospective cohort study of asymptomatic nulliparous women with a singleton gestation. Participants underwent CL measurement by transvaginal ultrasound between 20 and 24 weeks of gestation. The participants and their health care providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Additionally, Sawaddisan et al [16] reported that a UCA ≥ 110° measured later than 19.5 weeks of gestation corresponded to an 83.3% sensitivity for predicting spontaneous PTB. A study conducted by Paul Guerby et al [31] revealed that a mid-trimester CL < 30 mm could detect 35% of all spontaneous PTBs before 35 weeks gestation at a false-positive rate of 5% in low-risk nulliparous women. It is important to note that their study included only women with no previous pregnancies, and ultrasound was conducted between 20 and 24 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sawaddisan et al [16] reported that a UCA ≥ 110° measured later than 19.5 weeks of gestation corresponded to an 83.3% sensitivity for predicting spontaneous PTB. A study conducted by Paul Guerby et al [31] revealed that a mid-trimester CL < 30 mm could detect 35% of all spontaneous PTBs before 35 weeks gestation at a false-positive rate of 5% in low-risk nulliparous women. It is important to note that their study included only women with no previous pregnancies, and ultrasound was conducted between 20 and 24 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include maternal, fetal, biological and genetic variables [9,10]. While the predictive value of cervical length measurement by transvaginal ultrasound (TVS) has been established [11], identification of women at risk of spontaneous PTB by other techniques remains a major challenge [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors include maternal, fetal, biological, and genetic variables [9,10]. While the predictive value of cervical length measurement by transvaginal ultrasound (TVS) has been established [11], the identification of women at risk of spontaneous PTB by other techniques remains a major challenge [12,13,14]. Accordingly, cervical shortening is the most commonly used inclusion criterion for trials evaluating the prevention of preterm birth in singleton pregnancies by placement of a cervical pessary.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have questioned the predictive performance of a short cervical length of less than 30 mm compared to that of less than 25 mm and suggested that a cut-off of 30 mm in the second trimester of pregnancy may more accurately predict the risk of PTB before 35 and 37 weeks of gestation (AUC: 0.70) [ 19 ]. However, the majority of observational studies reported a cut-off of 2.5 cm [ 20 , 21 , 22 ], which demonstrated a moderate predictive performance.…”
Section: Introductionmentioning
confidence: 99%